Implementasi Program Pelayanan Kesehatan Posyandu Mawar dalam Menekan Angka Stunting di RW 15 Kecamatan Tarogong Kidul Kabupaten Garut - Yabes Anugerah; Rahayu Mukti Fatonahningsih; Asep Muhidin Abdul Zaelani; Syira Nurliana Aqilah; Wilya Khodizatul Kurnia; Rizky Ilhami (Lembaga Pengembangan Kinerja Dosen, 2026)
Stunting is a chronic nutritional problem that impacts children's physical growth and cognitive development and poses a serious challenge to improving the quality of human resources in Indonesia. Garut Regency still faces high stunting rates, particularly in neighborhood unit (RW) 15, Jayaraga Village, Tarogong Kidul District. Through this Community Service Program (PKM), the team is working to reduce stunting rates by implementing health services at the Mawar Integrated Health Post (Posyandu Mawar). This program aims to increase community knowledge about the importance of balanced nutrition, exclusive breastfeeding, and monitoring child growth and development. Activities include outreach, toddler examinations, and training on making supplementary foods using local ingredients, involving Posyandu cadres and local health workers. Results indicate increased public understanding and awareness of stunting prevention and increased community participation in Posyandu activities. This program is considered effective in strengthening the role of Posyandu as the frontline provider of public health services, although program sustainability and cross-sector synergy are still needed to achieve optimal results.